2022
DOI: 10.1007/s00281-022-00937-5
|View full text |Cite
|
Sign up to set email alerts
|

B cells in autoimmune hepatitis: bystanders or central players?

Abstract: B cells are central for the adaptive immune system to mount successful immune responses not only as antibody producers but also as regulators of cellular immunity. These multifaceted features are also reflected in autoimmunity where autoreactive B cells can fuel disease by production of cytotoxic autoantibodies, presentation of autoantigens to autoreactive T cells, and secretion of cytokines and chemokines that either promote detrimental immune activation or impair regulatory T and B cells. The role of B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 226 publications
0
12
0
2
Order By: Relevance
“…The depletion of B cells by rituximab is an alternative approach. However, the long-term use of these drugs in some patients may result in an increased risk of developing hypertension and diabetes [ 11 , 12 ].…”
Section: B Cells and Autoimmune Diseasesmentioning
confidence: 99%
“…The depletion of B cells by rituximab is an alternative approach. However, the long-term use of these drugs in some patients may result in an increased risk of developing hypertension and diabetes [ 11 , 12 ].…”
Section: B Cells and Autoimmune Diseasesmentioning
confidence: 99%
“…Der Nachweis von Autoantikörpern ist für keine der autoimmunen Lebererkrankungen pathognomisch und sollte immer im Zusammenhang und unter Beachtung sämtlicher klinischer Faktoren interpretiert werden, da sie auch bei anderen Autoimmunerkrankungen und sonstigen Lebererkrankungen auftreten können (s. Tab. 2 ) 4 , 5 .…”
Section: üBergreifende Aspekte In Der Diagnostik Und Therapieunclassified
“…Aktuell werden sowohl genetische als auch Umweltfaktoren diskutiert, die zur Dysregulation des Immunsystems mit der Folge einer T-Zell-getriebenen Zerstörung von Hepatozyten führt 12 . Das Vorhandensein einer selektiven IgG-Erhöhung sowie die Entwicklung von Autoantikörpern deuten auf eine Beteiligung von B-Zellen an der Pathogenese hin 5 .…”
Section: Autoimmune Hepatitis (Aih)unclassified
“…In the absence of other APCs, activation of CD4 + T cells and T follicular helper (Tfh) can be initiated by B cells. It has been reported that B cell-derived cytokines have double-edged effects on AIH ( 8 ). On one hand, pro-inflammatory cytokines like type I interferons, tumor necrosis factor-alpha (TNF-α), and interleukin (IL) 6 contribute directly or indirectly to disease progression.…”
Section: Introductionmentioning
confidence: 99%